Health Promoting Behaviors in Pregnant Women Admitted to the Prenatal Care Unit of Imam Khomeini Hospital of Saqqez - Hassan Mahmoodi*; Mohammad Asghari-Jafarabadi; Twohid Babazadeh; Younes Mohammadi; Shayesteh Shirzadi; Pershang Sharifi-Saqezi; Nian Mulodi-rad (Hamadan University of Medical Sciences, 2015)
Background and Objectives: Health promoting behaviors are crucial to the health of pregnant women and their children. The present study was conducted to assess health promoting behaviors in pregnant women admitted to Imam Khomeini Hospital of Saqqez. Materials and Methods: The present descriptive analytical study was conducted on 181 pregnant women selected through convenience sampling. The data collection tool used in the study was a questionnaire containing two parts: a section on the subjects' demographic details, and another section for the Health Promoting Lifestyle Profile II (HPLP II). Data were analyzed in SPSS-21 using descriptive (frequency percentage) and inferential statistics, such as the independent t-test, the Pearson correlation test and the one-way ANOVA. Results: Based on the findings of the study, the highest scores of health promoting behaviors obtained were in the domain of spiritual growth and the lowest in the domain of physical activity. The mean overall score of health promoting behaviors was desirable. The only demographic variable found to have a significant relationship with health promoting behaviors was occupation (P<0.032). Conclusion: The results obtained indicate desirable levels of health promoting behaviors in these pregnant women. Other domains of health such as physical activity, stress management and accountability are recommended to be further emphasized. Future studies are encouraged to be conducted on other ethnicities and with larger sample sizes.